Struktura kapituły uniejowskiej w świetle Liber beneficiorum Jana Łaskiego - Jabłońska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2001)
Each chapter consisted of the following elements: place, system of dignilies-offices, allotted real properly and people. In the case of the Chapter of Uniejów, a fairly complete description of the above-mentioned elements was described as late as the beginning of the XVIth century. The source of this description is the Liber beneßeiorum by Jan Łaski. It is well attested that there was Virgin Mary and St. Florian chapter, which was established most probably in the year 1170 and later re-founded in the year 1365. It consisted of two prelate’s dignities; praeposite (the first dignity) and archdeacon, 5 canonries, 7 vicariates and a, created in the year 1365, praepositure „a capellis s. Nicolai” and its vicarage; all of the dignities used to be taken by the Benedictines from Tyniec, and also by a simple benefice, which was constituted by the altaria „Adae”. It was as late as the year 1529, when Jan Łaski established a custodia. Finally, a deacon’s dignity was created by Mikołaj Lubieński in the year 1648. The Chapter played also the role of a local, both urban and rural, parish. The vice-praeposite was in charge of „cura animarum" of the rural part, while the urban section was seen to by those who were nominated to the archdeacon’s vicarage. There had also been 7 presbyters who constituted a „universitas mansionariorum” and manned the parish in Spicimierz since the year 1491. The vicars constituted a „universitas” of their own. The value of the common property and each prebend was a function of the following elements: permanent and temporary income (both urban and rural), produced merchandise, money, services, estates, tithes, rent and colenda. It should be also concluded that the Chapter of Uniejów belonged to neither the most renowned nor wealthiest in the metropolitan Church district of Gniezno.